Sintering-resistant metal material
By preparing a metal material of specific composition, including components such as Sn, Mo, Fe, W, S and graphite, and using isostatic pressure and sintering processes, the problem of sintering of existing metal materials at high temperatures and high surface pressures is solved, and significant sintering resistance and rust resistance are achieved.
Patent Information
- Application Number
- CN202510003424.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-08
AI Technical Summary
Existing metal materials are prone to sintering under high temperature and high surface pressure, resulting in wear, melting and carbonization, and losing their sintering resistance.
A sintering-resistant metal material is used, which consists of 4 wt% to 6 wt% Sn, 8 wt% to 12 wt% Mo, 3 wt% to 5 wt% Fe, 0.5 wt% to 1 wt% W, 0.15 wt% to 0.3 wt% S, 1 wt% to 1.5 wt% graphite, and lubricating organic polymers and anti-rust lubricating inorganic salts as auxiliary components. The material is prepared by isostatic pressure and sintering processes to ensure uniform distribution of components and lubrication of polymers in the grain boundaries.
It significantly improves the material's sintering resistance under high strength pressure and friction, avoids the occurrence of sintering, and maintains the material's wear and rust resistance.
Smart Images

Figure CN119776695A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a metal material having multiple components, and in particular to a sintering-resistant metal material. Background Art
[0002] With the rapid development of industrial upgrading and various industrial sectors, existing material products need to be continuously improved according to industrial upgrading. For example, with the development of new energy industry, in industries such as new energy vehicles, the output power of automobiles and the level of various mechanical configurations are getting higher and higher. Under the driving force of larger motors, the bearings of the products need to bear greater pressure between the contact surfaces, and the requirements for the matching and docking of metal products are getting higher and higher. For example, inside the engine or motor, between the surfaces of the bearing mating surfaces sliding and rubbing at high speed, copper alloy sliding materials are often encountered. The fatigue resistance is poor at high surface pressure, and if the sliding surface reaches a high temperature, it cannot maintain sintering resistance due to the outflow or depletion of part of the low-temperature phase. Under high temperature and high surface pressure, although there will be a certain lubrication environment under actual working conditions, they will still cause "sintering" phenomenon. After the "sintering" phenomenon occurs, the surfaces of the metal materials in contact with each other will wear, melt, and carbonize at high temperature and separate from the metal matrix, resulting in the tolerance matching and working conditions of the surfaces of the workpieces in contact with each other no longer being met or significantly deteriorating.
[0003] In this regard, there have been many studies and reports on the sintering resistance of surface-joined metal materials. For example, Chinese patent publication CN109536773A reports a copper alloy material, preparation method and application. The patent technology believes that the prepared alloy material has good tensile strength and excellent sintering resistance. However, not only does the significant Pb lead component contained in this type of material not meet the increasingly stringent environmental protection requirements, but this type of research has also failed to effectively solve and focus on the wear and loss of the surface "sintering" under high-intensity friction conditions on the contact surface. Summary of the invention
[0004] The present invention aims to solve one or more deficiencies in the above-mentioned prior art, and provides a sintering-resistant metal material, characterized in that, calculated by mass percentage, the sintering-resistant metal material comprises the following components:
[0005] 4 to 6 wt % Sn;
[0006] 8 to 12 wt% Mo;
[0007] 3 to 5 wt% Fe;
[0008] 0.5 to 1 wt% W;
[0009] 0.15 wt % to 0.3 wt % S;
[0010] 1 wt % to 1.5 wt % of graphite; and
[0011] Auxiliary components, which include a lubricating organic polymer component, which accounts for 0.15wt% to 0.6wt% of the sintering-resistant metal material; and a rust-proof lubricating inorganic salt component, which accounts for 0.1wt% to 0.2wt% of the sintering-resistant metal material; and
[0012] The balance is Cu and inevitable impurities.
[0013] In a preferred embodiment, the lubricating organic polymer component is selected from one or both of polyethylene wax and polytetrafluoroethylene; the rust-proof lubricating inorganic salt component is selected from one or both of magnesium hypophosphite and sodium tetraborate; and
[0014] Preferably, the lubricating organic polymer component and the rust-proof lubricating inorganic salt component are distributed in a matrix of the sintering-resistant metal material.
[0015] In a further optional solution, the sintering-resistant metal material is prepared from the following raw materials by isostatic pressing and sintering:
[0016] The raw materials include Cu powder, CuSn alloy powder, Fe-Mo alloy powder, tungsten disulfide (WS2) powder, graphite powder, polyethylene wax powder, polytetrafluoroethylene powder, magnesium hypophosphite powder and sodium tetraborate powder; and, preferably, the average particle size (D50) of each raw material powder is between 80μm and 120μm.
[0017] In a further preferred embodiment, the raw material is prepared in sequence by a cold isostatic pressing process, a hot isostatic pressing process at 100°C to 120°C, a sintering process at 700°C to 800°C for 30 seconds to 60 seconds, and a cold rolling process.
[0018] In a further optional solution, the sintering-resistant metal material is specifically obtained by a preparation step comprising the following processes:
[0019] Raw material preparation steps: Prepare various raw materials based on the total mass of sintering-resistant metal materials, including: Cu powder, Cu with an element mass ratio of 9:1 90 Sn 10 Powder, FeMo alloy powder, tungsten disulfide (WS2) powder, graphite powder, polyethylene wax powder, polytetrafluoroethylene powder, magnesium hypophosphite powder and sodium tetraborate powder in an element mass ratio of (20-50): (50-80);
[0020] Cold isostatic pressing step: fully mix the powders of the above raw materials in a mixer in a nitrogen atmosphere, then put the mixed powder into a rubber bag to exclude air and seal it, and then seal it after shaking it, place it in the cavity of the cold isostatic press, and then start to inject liquid pressure medium into the cavity of the cold isostatic press until it is full, and then increase the pressure to 350Mpa to 400Mpa, and the cold isostatic pressing preparation time is 10 minutes to 15 minutes; obtain a cold isostatic pressed blank;
[0021] Hot isostatic pressing process: the temperature of the isostatic pressing equipment is raised to 100°C to 120°C, the isostatic pressing pressure is set to 300Mpa to 350Mpa, and the obtained cold isostatic pressed blank is subjected to hot isostatic pressing for 20 minutes to 30 minutes while maintaining the pressure and temperature to obtain a hot isostatic pressed blank;
[0022] High temperature hot sintering process: placing the obtained hot isostatic pressed blank into a sintering furnace, flushing nitrogen to expel the air, and then evacuating the furnace, heating the sintering furnace to 700°C to 800°C at a rate of 100 to 150°C / second, and keeping the temperature for 30 to 60 seconds; then, charging the reactor with circulating cold nitrogen at 10 to 15°C to cool it down until the temperature of the alloy material drops below 50°C; obtaining a sintered blank;
[0023] Cold rolling step: sending the obtained sintered blank into a cold rolling production line, the cold rolling temperature is room temperature, the cold rolling speed is 60mm / min to 100mm / min, and the single pass reduction of cold rolling is 5% to 10% calculated as a percentage of the initial blank thickness, until a thickness of 2cm to 5cm is obtained to obtain the sintering-resistant metal material.
[0024] Further, preferably, in the prepared sintering-resistant metal material, polyethylene wax accounts for 0.1wt% to 0.3wt% of the total mass of the sintering-resistant metal material, polytetrafluoroethylene accounts for 0.05wt% to 0.15wt% of the total mass of the sintering-resistant metal material, and magnesium hypophosphite and sodium tetraborate each account for 0.05wt% to 0.1wt% of the total mass of the sintering-resistant metal material.
[0025] According to the material prepared by the present invention, the sintering-resistant metal material does not undergo sintering under the following test conditions; wherein the sintering phenomenon is defined as:
[0026] The sintering-resistant metal material is closely contacted with the surface of the sample disk, and the contact area between the metal material and the surface of the sample disk is 25 cm 2 , a force of 500kg / cm2 is applied to the contact surface in the vertical direction of the contact surface. 2 Under the conditions of surface pressure, relative rotation of the material contact surface at a linear speed of 0.5 m / s calculated on the circumference, and maintaining for 60 minutes, the wear thickness of the metal material surface exceeds 50 μm.
[0027] The sintering-resistant metal material and preparation process according to the present invention significantly improve the "sintering" problem of the material contact surface under high-intensity pressure and friction, and provide a metal material with potential for precision and high-power mechanical equipment.
[0028] In the following, the technical solutions and advantages of the present invention will be explained and described in more detail in conjunction with specific implementation methods. It should be understood that the contents presented in the specification and specific implementation methods are only for the purpose of more clearly illustrating the technical solutions and advantages of the present invention, and do not limit the protection scope of the present invention. Those skilled in the art can obtain the changed technical solutions based on the disclosure of the specification for various reasonable transformations. As long as they do not deviate from the spirit of the present invention, the various changed technical solutions should be understood to be included in the protection scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings are used to provide a further understanding of the technical solution of the present disclosure and constitute a part of the specification. Together with the specific embodiments of the present application, they are used to explain the technical solution of the present disclosure and do not constitute a limitation on the technical solution of the present disclosure.
[0030] Figure 1 is a schematic diagram of a testing device for testing sintering resistance according to the present invention;
[0031] Figure 2 This is a surface SEM scanning electron microscope picture of the metal material prepared according to Example 1 of the present invention after being subjected to a sintering resistance test. DETAILED DESCRIPTION
[0032] The present invention is described in more detail hereinafter to facilitate understanding of the invention.
[0033] Before describing the specific implementation scheme, it should be noted that those skilled in the art can select appropriate raw materials according to the enlightenment and teaching of the present disclosure, and use relevant testing equipment to perform relevant tests and obtain corresponding results. For raw materials without specific manufacturers or pathways, those skilled in the art can select raw materials that meet corresponding requirements as reaction starting materials according to the disclosure and requirements of this specification. The reaction raw materials of the process part compounds are derived from the initial products synthesized in the preamble step of the present invention, which can also be understood according to the present disclosure.
[0034] First, the main raw materials used in the present invention and the corresponding acquisition channels or raw material origins are listed in Table 1. It should be noted that the raw materials not described in the present invention are raw material varieties that can be obtained by those skilled in the art based on common technical knowledge and existing market products.
[0035] Table 1: Description of the main raw materials used in the present invention
[0036]
[0037]
[0038] About the sintering resistance test
[0039] In the technical field, especially between the surfaces of the bearing joints that slide and rub against each other at high speed, copper alloy sliding materials are often encountered with poor fatigue resistance under high surface pressure, and if the sliding surface reaches a high temperature, it cannot maintain sintering resistance due to the outflow or depletion of some low-temperature phases. Under high temperature and high surface pressure, although there will be a certain lubrication environment under actual working conditions, "sintering" will still occur between them. After the "sintering" phenomenon occurs, the surfaces of the metal materials in contact with each other will wear, melt, and carbonize at high temperatures and separate from the metal matrix, resulting in the tolerances and working conditions of the surfaces of the workpieces in contact with each other no longer being met or significantly deteriorating.
[0040] In this experimental example, each metal, polymer and non-metal raw material is a powdered raw material with an average particle size (D50) of less than 200 microns, preferably less than or equal to 150 microns. The usual raw material powder particle size D50 is preferably between 50 and 120 microns, which is conducive to the implementation of the isostatic pressing process and the subsequent sintering resistance test.
[0041] In order to characterize this "sintering" degradation phenomenon, a constant speed friction and wear test device can be used. In the test process described in this embodiment, Optimol produced by BRUKER, USA, was used. Series friction and wear test system. The schematic diagram of the test can be referred to Figure 1 As shown. Figure 1 In the test scheme, the metal material plate or blank 100 to be tested is pressed on a test disc 101 rotating at a constant speed of 0.5 m / s (the surface of the test disc has a high wear resistance surface, for example). After the pressure member 102 is in close contact with the blank 100 (the contact surface area of a typical test sample is about 25 cm 2 , which presents a square or circular surface), the applied surface pressure is stepped from 100kg / cm 2 Boost pressure to 900kg / cm 2 , every 100kg / cm 2 The pressure is increased, and each stage is maintained for 60 minutes. At the same time, the detection system provides an appropriate lubrication environment to control the friction coefficient of the contact surface between 0.1 and 0.12. Then, at a certain test stage, when the wear value exceeds the limit value, it is considered "sintering". In the experimental test description of this application, it can be defined that when the metal material is 900kg / cm2 Under the surface pressure of 0.5m / s (circumference calculated linear speed) and maintained for 60 minutes, the wear (or loss) of the metal material surface thickness does not exceed 20μm, which is considered to be "unsintered" (or "non-sintered" or excellent wear performance). As the lower limit of the test experiment, it is considered that at a certain test stage (such as 300, 400, 500kg / cm 2 ) surface pressure, the relative rotation speed of the material contact surface is 0.5m / s (circumference calculated linear speed, the rotating table is a 10cm diameter circular table), and the wear (or loss) of the metal material surface thickness exceeds 50μm, which is "sintering" (or wear performance degradation). In this regard, it is generally believed that if the material is under 500kg / cm 2 At a surface pressure of or below, the corresponding surface wear thickness exceeding 50μm is unqualified. In the field of precision machinery with strict tolerance requirements, it is generally believed that wear above this amount is inconsistent with the tight fit between mechanical components and working conditions, or does not meet the requirements. Figure 1 The material thickness variations in the figure are exaggerated for clarity of illustration.
[0042] In addition, it should be noted that the product components or method processes of the present invention may include the components described accordingly and also contain other components or processes. However, in a preferred embodiment, the metal material components of the present invention may also consist of only the components or processes described above and no longer contain any other or significant components / processes.
[0043] Example
[0044] This embodiment describes the preparation process of the sintering-resistant metal material and the corresponding component composition.
[0045] First, the main matrix material component, the auxiliary element component, and the auxiliary element component (initial composition) are weighed according to the composition shown in the following table (Table 2); wherein each component is provided in the form of powder. In a typical embodiment, the main matrix material is composed of Cu powder and Cu 90 Sn 10 powder (mass ratio 9:1), calculated based on the total mass of sintering resistant metal materials, Cu 90 Sn 10 The powder accounts for 45-65wt%, so that the content of Sn metal element is about 4wt% to 6wt%; the auxiliary element components include Mo, Fe-Mo alloy (quality formula Fe 30 Mo 70 , Fe 40 Mo 60 , Fe 50 Mo 50 , Fe20 Mo 80 ), tungsten disulfide (WS2) and graphite, wherein the mass of Fe element is controlled to be 3-5wt% of the total mass, Mo element accounts for 8-12wt% of the total mass of the total metal material; W accounts for 0.5wt% to 1wt% of the total mass of the total metal material, S accounts for 0.15wt% to 0.3wt% of the total mass of the elements, and graphite accounts for 1wt% to 1.5wt% of the total mass.
[0046] The auxiliary components in typical embodiments include high molecular polymers and inorganic salts. Their combination with the above-mentioned main components and auxiliary element components greatly improves the sintering resistance of the metal material. In typical embodiments, polyethylene wax, polytetrafluoroethylene, magnesium hypophosphite and sodium tetraborate. According to different embodiments, polyethylene wax accounts for 0.2wt% to 0.5wt% of the total mass of the sintering-resistant metal material, polytetrafluoroethylene accounts for 0.1wt% to 0.2wt% of the total mass of the sintering-resistant metal material, and magnesium hypophosphite and sodium tetraborate each account for 0.05wt% to 0.1wt% of the total mass of the sintering-resistant metal material.
[0047] Table 2: Composition of sintering-resistant metal materials of the embodiment (wt%)
[0048]
[0049] After the components are determined, a mixer is used to uniformly mix the powders.
[0050] In order to ensure that most of the organic components are retained inside the metal material matrix, a typical implementation process of the present invention adopts cold isostatic pressing, hot isostatic pressing (relative temperature), and short-time high-temperature sintering processes for preparation.
[0051] Cold isostatic pressing step: putting the alloy material powder into a rubber bag to exclude air and seal it, and then sealing it after vibrating it, and then placing it in the cavity of the cold isostatic press, and then starting to inject liquid pressure medium into the cavity of the cold isostatic press until it is full, and then increasing the pressure to 380Mpa, and the cold isostatic pressing preparation time is 12 minutes; obtaining a cold isostatic pressed blank;
[0052] Hot isostatic pressing process: the temperature of the isostatic pressing equipment is raised to 120°C, the isostatic pressing pressure is set to 350 MPa, and the pressure and temperature are maintained for hot isostatic pressing for 30 minutes to obtain a hot isostatic pressed blank;
[0053] High temperature hot sintering process: Place the hot isostatic pressed blank into a sintering furnace, flush with nitrogen to expel the air, then evacuate (typical vacuum pressure 0.01Mpa), heat up to 750℃ at a rate of 150℃ / second, keep warm for 40 seconds, then fill the reactor with circulating cold nitrogen at 10℃ to 15℃ to cool down until the temperature of the alloy material drops below 50℃; obtain a sintered blank;
[0054] Cold rolling steps: The cold rolling temperature is room temperature, the cold rolling speed is 60 mm / min, and the single-pass cold rolling reduction is 5% (as a percentage of the initial blank thickness) until a thickness of 3 cm is obtained. Cutting is performed according to the test environment to obtain metal material plates for subsequent processing or testing.
[0055] This experimental example adopts a long period of cold isostatic pressing process, combined with a hot isostatic pressing process at an intermediate temperature, and a very short high-temperature sintering step (which is conducive to the formation of intermetallic phases by metal elements to improve toughness), which can effectively retain the flow and original state of trace polymer phases between the metal material matrix. Generally, polyethylene wax and polytetrafluoroethylene can be mostly distributed in the metal material matrix in a uniform form; or the loss of polyethylene wax and polytetrafluoroethylene after each processing process is less than 30%wt, or less than 50wt%. In the final components of the synthesized metal material, for example, polyethylene wax accounts for 0.1wt% to 0.3wt% of the total mass of the sintering-resistant metal material, polytetrafluoroethylene accounts for 0.05wt% to 0.15wt% of the total mass of the sintering-resistant metal material, and the content of other components (metal elements, non-metallic elements resistant to long-term high temperature, and inorganic compounds) remains basically unchanged.
[0056] Comparative Examples 1-5
[0057] In the first series of comparative experiments, the same preparation process as in the example was used, except that the proportions or types of components in the example were adjusted, as shown in the following table.
[0058] Table 3: Distribution ratio of each group of metal materials in comparative experiments
[0059] Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Cu margin margin margin margin margin Sn 10 5 6 6 6 Mo 10 8 9 10 10 Fe 5 2.5 5 5 5 W 0.5 1 - 0.5 0.5 S 0.17 0.34 0.2 0.17 0.17 graphite 1 1 1 1 - Polyethylene wax 0.5 0.3 0.3 - 0.5 Polytetrafluoroethylene 0.1 0.1 0.1 0.6 0.1 Magnesium Hypophosphite 0.05 0.1 0.1 0.2 0.05 Sodium Tetraborate 0.1 0.1 0.1 - 0.1
[0060] In this series of comparative examples, Comparative Example 1 significantly increased the Sn component in the metal material, raising the proportion to 10wt% of the total mass; in Example 2, the content of the Fe element was significantly reduced, and some metal Mo powder was additionally used as a raw material component; in Example 3, no W element was added, and molybdenum disulfide (MoS2) was used as a raw material component instead of WS2; in Comparative Example 4, only polytetrafluoroethylene was used as the polymer among the auxiliary elements and only magnesium hypophosphite was used as the inorganic salt; in Comparative Example 5, graphite was no longer used as a secondary component.
[0061] Comparative Example 6
[0062] In Comparative Example 6, a metal material preparation process similar to that of the embodiment series is adopted, except that, among the raw material components, Sn accounts for 6wt%, Mo accounts for 10wt%, Fe accounts for 5wt%, W accounts for 0.5wt%, sulfur accounts for about 0.17wt%, and graphite accounts for about 1wt%, which is basically the same as the composition of Example 1; however, in the metal material system, auxiliary components are no longer used. Instead, the above-mentioned main components are subjected to the manufacturing process of the embodiment and then attached to the surface of the metal material by impregnation coating with a solution of the auxiliary components.
[0063] More specifically, a mixed dispersion of 10wt% polyethylene wax powder, 10wt% polytetrafluoroethylene, 10wt% magnesium hypophosphite, 10wt% sodium tetraborate, 30wt% 95% anhydrous ethanol, and 30wt% deionized water is prepared. After the preparation of the main material is completed, the main material is immersed in the above dispersion for 60 minutes to complete the coating and wrapping of the auxiliary components on the main material. Thereafter, the prepared material component is also subjected to the test described in this embodiment.
[0064] Test results and analysis
[0065] The above examples and comparative examples were subjected to the sintering resistance test described in the specification. Specifically, the samples were applied to a workbench, and the surface pressure applied was stepped from 100 kg / cm 2 Boost pressure to 900kg / cm 2 , every 100kg / cm 2 The pressure was increased and each stage was maintained for 60 minutes. When it was found that the thickness of the material "sintered" (lost) within 60 minutes exceeded 50 microns at a certain stage, the test was stopped and it was considered to be the maximum sintering resistance that the material could achieve. The test results are shown in the table below.
[0066] Table 4: Sintering resistance test results of examples and comparative examples
[0067] Test example <![CDATA[Surface pressure resistance (kg / cm 2 )]]> Sintered amount (μm) Example 1 900 10 Example 2 900 25 Example 3 900 18 Example 4 900 28 Comparative Example 1 700 45 Comparative Example 2 700 58 Comparative Example 3 800 45 Comparative Example 4 700 49 Comparative Example 5 700 40 Comparative Example 6 600 45
[0068] It can be seen from the implementation scheme and comparative experiments that the metal material of the implementation scheme of the present invention has obtained the relatively most excellent sintering resistance property.
[0069] The metal materials of Examples 1 to 4 can withstand 900 kg / cm 2 The pressure wear and tear of the metal material is maintained within the test time of 60 minutes with a sintered (loss) thickness of less than 50 microns, or even less than 30 microns. In contrast, when the metal part of the metal material exceeds the scope of the present invention, the sintering resistance of the metal material is relatively deteriorated.
[0070] In this regard, the inventors conducted a study on the metal sheet of Example 1 subjected to 900 kg / cm 2 The surface after the pressure sintering test was characterized by SEM scanning electron microscopy, such as Figure 2 shown. Figure 2 It can be seen that the surface particle size of the metal material after isostatic pressing and cold rolling process has grown, and the grains may further grow and fuse during the high heat wear test. Although the surface of the SEM photo shows obvious scratches between the grains in the horizontal direction, the grains are tightly connected and smooth, and the boundaries between the grains are smooth, with almost no obvious protrusions, which keeps the friction force and friction coefficient from further abnormally increasing, and maintains good sintering resistance. In addition, it can be seen from the SEM picture that the grain boundaries are relatively clear. The inventor believes that it is not subject to any theory. This may be related to the lubrication and cruising of polyethylene wax and polytetrafluoroethylene between the grain boundaries. After the polymer is melted, it has the opportunity to diffuse between the grain boundaries during the hot isostatic pressing and rapid sintering in an inert atmosphere, increasing lubricity and avoiding the loss of the grains themselves. In addition, the obvious black spots are related to the presence of inorganic compounds, which have a pinning effect on the grains and enhance the series effect between the grains. Among them, magnesium hypophosphite helps to reduce the friction coefficient, and sodium tetraborate dispersed in the matrix can also effectively prevent the rust of Fe-containing grains, which also plays an auxiliary role under high temperature conditions.
[0071] Compared with the embodiment, the sintering resistance and wear characteristics of the comparative experiment are deteriorated. When the Sn content is too high (greater than 6wt%) and the Fe content is too low (less than 4wt%), the sintering resistance is deteriorated. Sn is generally considered to be a soft phase in the Cu-Sn alloy system. The soft crystal phase helps to increase the toughness of the metal material under normal pressure, but when the external wear pressure is too large (greater than 700, or even greater than 800kg / cm 2 ), the soft phase grains may cause deformation of the worn surface locally, resulting in abnormal increase of local friction and increased wear. In this embodiment, the Fe-Mo intermediate phase is formed by the high temperature and wear resistance of the Fe-Mo alloy. If the Fe content is less than 4wt%, the proportion of the sintering-resistant intermediate phase is reduced. At the same time, the inventors found that the Fe-Mo intermediate phase is conducive to the flow and lubrication of the polymer components between the grains, reducing the proportion of large grains.
[0072] In addition, the diffusion and movement of the two polymer components and two inorganic salts in the metal material matrix of the present invention are conducive to increasing the rust resistance of the matrix, reducing the lubrication properties of the matrix part and the bonding force of the grains, and can also effectively prevent the abnormal growth of the grains, resulting in uneven surface force and local deformation. When there is only one polymer material, for example, polytetrafluoroethylene has strong high temperature resistance, but relatively poor fluidity. It is worth noting that graphite, as a conventional lubricating component, is also very effective in combination with other components. When graphite powder is not used at all, the lubrication properties are insufficient.
[0073] In addition, the inventors found that when the auxiliary component is used as a covering layer to coat the tested metal material, under low pressure test conditions (less than or equal to 500 kg / cm 2 ), which contributes to the anti-wear and lubrication properties. However, when the test pressure becomes severe, the anti-wear and lubrication materials covering the surface cannot effectively improve and prevent the anti-sintering properties, and the anti-sintering properties are insufficient compared to the metal materials with related materials dispersed in the matrix. This is related to the insufficient adhesion of the covering layer and the particles being worn away at the beginning of contact with the large pressure, resulting in the internal material layer being unable to be protected.
[0074] According to the implementation scheme and technical contents recorded in the specification of the present invention, the present invention can at least provide the following technical solutions: Although the present disclosure includes specific embodiments, it is obvious to those skilled in the art that various formal and detailed replacements or changes can be made to these embodiments without departing from the gist and scope of the invention of the present claims and their equivalent technical solutions. The embodiments described herein should be considered to be illustrative only and not for the purpose of limitation. The description of the features and aspects in each embodiment is considered to be applicable to similar features and aspects in other embodiments. Therefore, the scope of the present disclosure should not be limited by the specific description, but by the technical solutions of the claims, and all changes within the scope of the claims and their equivalents are interpreted as being included in the technical solutions of the present disclosure.
Claims
1. A sintering-resistant metal material, characterized in that: Calculated by mass percentage, the sintering-resistant metal material includes the following components: 4 to 6 wt % Sn; 8 to 12 wt% Mo; 3 to 5 wt% Fe; 0.5 to 1 wt% W; 0.15 wt % to 0.3 wt % S; 1 wt % to 1.5 wt % of graphite; as well as an auxiliary component comprising a lubricating organic polymer component which accounts for 0.15 wt % to 0.6 wt % of the sintering-resistant metal material; and a rust-proof and lubricating inorganic salt component, which accounts for 0.1wt% to 0.2wt% of the sintering-resistant metal material; and The balance is Cu and inevitable impurities.
2. The sintering-resistant metal material according to claim 1, characterized in that: The lubricating organic polymer component is selected from one or both of polyethylene wax and polytetrafluoroethylene; the rust-proof lubricating inorganic salt component is selected from one or both of magnesium hypophosphite and sodium tetraborate; and Preferably, the lubricating organic polymer component and the rust-proof lubricating inorganic salt component are distributed in a matrix of the sintering-resistant metal material.
3. The sintering-resistant metal material according to claim 1 or 2, characterized in that: The sintering-resistant metal material is prepared from the following raw materials through isostatic pressing and sintering processes: The raw materials include Cu powder, CuSn alloy powder, Fe-Mo alloy powder, tungsten disulfide (WS2) powder, graphite powder, polyethylene wax powder, polytetrafluoroethylene powder, magnesium hypophosphite powder and sodium tetraborate powder; and, preferably, the average particle size (D50) of each raw material powder is between 80μm and 120μm.
4. The sintering-resistant metal material according to any one of claims 1 to 3, characterized in that: The raw material is prepared in sequence through a cold isostatic pressing process, a hot isostatic pressing process at 100° C. to 120° C., a sintering process at 700° C. to 800° C. for 30 seconds to 60 seconds, and a cold rolling process.
5. The sintering-resistant metal material according to any one of claims 1 to 4, characterized in that: The sintering-resistant metal material is specifically obtained by the preparation steps including the following processes: Raw material preparation steps: Prepare various raw materials based on the total mass of sintering-resistant metal materials, including: Cu powder, Cu with an element mass ratio of 9:1 90 Sn 10 Powder, FeMo alloy powder, tungsten disulfide (WS2) powder, graphite powder, polyethylene wax powder, polytetrafluoroethylene powder, magnesium hypophosphite powder and sodium tetraborate powder in an element mass ratio of (20-50): (50-80); Cold isostatic pressing step: fully mix the powders of the above raw materials in a mixer in a nitrogen atmosphere, then put the mixed powder into a rubber bag to exclude air and seal it, and then seal it after shaking it, place it in the cavity of the cold isostatic press, and then start to inject liquid pressure medium into the cavity of the cold isostatic press until it is full, and then increase the pressure to 350Mpa to 400Mpa, and the cold isostatic pressing preparation time is 10 minutes to 15 minutes; obtain a cold isostatic pressed blank; Hot isostatic pressing process: the temperature of the isostatic pressing equipment is raised to 100°C to 120°C, the isostatic pressing pressure is set to 300Mpa to 350Mpa, and the obtained cold isostatic pressed blank is subjected to hot isostatic pressing for 20 minutes to 30 minutes while maintaining the pressure and temperature to obtain a hot isostatic pressed blank; High temperature hot sintering process: placing the obtained hot isostatic pressed blank into a sintering furnace, flushing nitrogen to expel the air, and then evacuating the furnace, heating the sintering furnace to 700°C to 800°C at a rate of 100 to 150°C / second, and keeping the temperature for 30 to 60 seconds; then, charging the reactor with circulating cold nitrogen at 10 to 15°C to cool it down until the temperature of the alloy material drops below 50°C; obtaining a sintered blank; Cold rolling step: sending the obtained sintered blank into a cold rolling production line, the cold rolling temperature is room temperature, the cold rolling speed is 60mm / min to 100mm / min, and the single pass reduction of cold rolling is 5% to 10% calculated as a percentage of the initial blank thickness, until a thickness of 2cm to 5cm is obtained to obtain the sintering-resistant metal material.
6. The sintering-resistant metal material according to any one of claims 1 to 5, characterized in that: In the prepared sintering-resistant metal material, polyethylene wax accounts for 0.1wt% to 0.3wt% of the total mass of the sintering-resistant metal material, polytetrafluoroethylene accounts for 0.05wt% to 0.15wt% of the total mass of the sintering-resistant metal material, and magnesium hypophosphite and sodium tetraborate each account for 0.05wt% to 0.1wt% of the total mass of the sintering-resistant metal material.
7. The sintering-resistant metal material according to any one of claims 1 to 6, characterized in that: The sintering-resistant metal material does not undergo sintering under the following test conditions; wherein the sintering phenomenon is defined as: The sintering-resistant metal material is closely contacted with the surface of the sample disk, and the contact area between the metal material and the surface of the sample disk is 25 cm 2 , a force of 500kg / cm2 is applied to the contact surface in the vertical direction of the contact surface. 2 Under the conditions of surface pressure, relative rotation of the material contact surface at a linear speed of 0.5 m / s calculated on the circumference, and maintaining for 60 minutes, the wear thickness of the metal material surface exceeds 50 μm.
Citation Information
Patent Citations
Copper alloy material, preparation method and application
CN109536773A
A copper-molybdenum alloy material with high conductivity and high wear resistance and its preparation method
CN102268566A
High-strnegth self-lubricating composite material for high-temperature use and process for producing the same
CN1149321A
Copper / graphene gradient composite material and preparation method thereof
CN118480716A